Repair of major road embankment failure using reinforced earth (re) wall - Jamalludin, Damanhuri; Ahmad, Mohd Farid; Mohd Salleh, Samsuri; Md. Issa, Ahmad Kamal (Universiti Teknologi MARA, Perlis, 2010)
A case history of repair works of major road embankment failure along Genting Highlands to Bukit Cincin, Pahang is presented. Failures at 10 locations along Genting Highlands to Bukit Cincin road occurred on 30th October 1997 during the monsoon seasons. The repair works at Location 1 using reinforced earth wall was considered since there was enough space available at the downslope section and also the soil at the downslope section of the failed embankment was strong enough to construct the wall safely. This paper fully explained the details remedial works using reinforced earth wall at Location 1.